Recontextualizing Arabic Reading Instruction: Developing Arabic Reading Skills Teaching Materials Grounded in Islamic Values - Hamidah; Abdullah (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to develop Maharah al-Qirā’ah (Arabic reading skills) instructional materials that integrate Islamic values and are contextualized to students’ social and proficiency levels. Utilizing a Research and Development (R&D) approach adapted from the Borg & Gall model, the research followed eight key stages, including preliminary research, planning, product development, field testing, revision, and implementation. Conducted at a single Islamic higher education institution, the study found that the developed materials significantly improved students’ reading comprehension of Arabic texts and positively influenced their affective and social engagement, including motivation and active participation. Validation by experts confirmed the materials’ feasibility, with recommendations for refining text structure and grammar. Theoretically, this research contributes to the Value-Based Content and Language Integrated Learning (VB-CLIL) paradigm by positioning Arabic reading instruction as a vehicle for values education, character building, and Islamic identity formation. The developed model is adaptable for implementation across similar Islamic educational contexts.